Variable waveform amplitude for a microchannel with single-wavy-wall boundary - Ong, Kun Wei (2019)
Introducing wavy profiles to the walls of a microchannel is a common modification done in hopes of improving thermal and hydraulic performance. The use of wavy profiles induces vortices that improves heat transfer performance but also induces an additional loss in pressure along the flow direction and thus requires additional pumping power. Most studies investigate and compare microchannels with walls that have wavy profiles featuring waveforms of constant amplitude including single-wavy- wall microchannels. However, the use of single-wavy-wall microchannel with variation in the amplitude of the waveform along the flow direction is a novel concept and the extent of the thermal and hydraulic performance is relatively unknown. In this project, an insert with a wavy surface has been manufactured and inserted concentrically into a hollow channel, forming an annular channel with a flat heating surface and a non-heated wavy boundary which is similar to implementation by previous studies. With this, a 300 μm annular channel is produced with single-wavy- wall profile aimed to enhance heat transfer of the channel. Three different inserts have been manufactured for this research to analyze the thermal and hydrodynamic effects of introducing waveforms with a step change in amplitude along the flow direction in a microchannel. Microchannels (Decreased Amplitude-DA and Increased Amplitude- IA) with waveforms that feature a step change in amplitude along the flow direction have waveform amplitudes of 0.05 mm and 0.15 mm, designed at opposite positions for DA and IA. A microchannel that has waveforms with constant average amplitude (Uniform Amplitude-UA) of 0.10 mm is also included in the study to serve as the reference. The project consists of two components. The first component involves collecting experimental measurements at flow rates from 1 to 7 liters per min under constant heat flux of 800 W with Reynolds number ranges from 550 to 3500. The second component utilizes a numerical prediction of the flow field at 2.5 and 4.5 liters per min to understand the flow field. The results show that by having a microchannel with waveforms that have a higher amplitude followed by a step decrease in amplitude along the flow direction (DA) result in better thermal performance compared to a microchannel with waveforms of constant amplitude (UA) at flow rates of 1 to 7 liters per min. However, the pressure drop incurred by DA and IA is higher than UA. Comparison to the plain microchannel shows that UA has the highest efficiency of 1.57 at 4 W of pumping power when factoring in both thermal and hydrodynamic considerations. This implies that UA can remove 57 % more heat as compared to a plain microchannel with the same given pumping power of 4 W. UA outperforms DA and IA at 2 to 7.5 W of pumping power. At low pumping power of 0.5 to 1.5 W however, DA performs the best with the maximum efficiency of 1.48 at 1.5 W. The numerical prediction shows that the single-wavy-wall microchannel is able to create sufficient perturbations to improve heat transfer performance. The better thermal capability of DA is due to the enhancement of fluid mixing downstream as a result of the high amplitude of the upstream waveforms.